A plague of rats and rubbervines : - Baskin, Yvonne (Island Press, 2002)
The human love of novelty and desire to make one place look like another, coupled with massive increases in global trade and transport, are creating a growing economic and ecological threat. The same forces that are rapidly "McDonaldizing" the world's diverse cultures are also driving us toward an era of monotonous, weedy, and uniformly impoverished landscapes. Unique plant and animal communities are slowly succumbing to the world's "rats and rubbervines" -- animals like zebra mussels and feral pigs, and plants like kudzu and water hyacinth -- that, once moved into new territory, can disrupt human enterprise and well-being as well as native habitats and biodiversity.